2010
DOI: 10.1007/s00198-010-1228-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of whole-body vibration on BMD: a systematic review and meta-analysis

Abstract: We found significant but small improvements in BMD in postmenopausal women and children and adolescents, but not in young adults. WBV is a promising new modality, but before recommendations can be made for clinical practice, large-scale long-term studies are needed to determine optimal magnitude, frequency, and duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
127
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(137 citation statements)
references
References 36 publications
(115 reference statements)
2
127
1
7
Order By: Relevance
“…16,17,26 Long-term adaptations include increased isometric and dynamic leg strength 8,13 and bone density. 47 Though the shortterm effects of whole-body vibration training on lower extremity flexibility and jumping power are controversial, 7,11,21,42 in the long term, these parameters show improvements. 9,11,42 Further, Hilgers et al 15 recently demonstrated that whole-body vibration training increases walking performance in patients with multiple sclerosis, suggesting that vibration training may positively influence neuromotor control.…”
Section: T T Resultsmentioning
confidence: 99%
“…16,17,26 Long-term adaptations include increased isometric and dynamic leg strength 8,13 and bone density. 47 Though the shortterm effects of whole-body vibration training on lower extremity flexibility and jumping power are controversial, 7,11,21,42 in the long term, these parameters show improvements. 9,11,42 Further, Hilgers et al 15 recently demonstrated that whole-body vibration training increases walking performance in patients with multiple sclerosis, suggesting that vibration training may positively influence neuromotor control.…”
Section: T T Resultsmentioning
confidence: 99%
“…In fact, this could explain the differences between the effects on the hip and spine which could be found in the results of some previous studies. Along with the previously mentioned, a group of authors [62] stated that these differences could occur due to inadequate sample sizes in individual studies.…”
Section: The Effects Of Vibration Training On Bone Mineral Densitymentioning
confidence: 91%
“…With this in mind, the contraindication factors for the use of vibration training, enlisted by the manufacturers themselves [59][60][61] are: the existence of kidney or bladder stones, epilepsy, cancer, pacemaker, recent implantation or surgery, thrombosis, hernia, rheumatologic arthritis, migraine, some cardiovascular problems and spinal injuries. Slatkowska et al [62] stated that there is no risk of using vibration training, and that it represents a new, promising modality for improving the characteristics of the skeletal system in postmenopausal women, respectively, same authors stated that the whole body vibration training increases muscular strength and power and slows down bone mineral density loss. Also, Russo et al [38] reported that there were no adverse effects of vibration training for women in menopause and post menopause.…”
Section: Whole Body Vibration Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…1,9,[14][15][16] Whole-body vibration (WBV) has been reported as a potent intervention for maintenance and/or enhancement of bone tissue in people with low levels of BMD, in elderly post-menopausal women and in adolescents. [17][18][19] In SCI patients, a combination of standing and WBV increased BMD in the trunk and spine, 20 whereas low-magnitude WBV improved the deterioration of neither the BMD in the distal femur nor the microstructure in the proximal tibia. 21 On the other hand, WBV improved the biomechanical properties of bones, histomorphometric parameters of the trabecular area and BMC in ovariectomized rats 22,23 and also microarchitecture and macro-biomechanical parameters in the rats suspended from their tails.…”
Section: Osteoporosis Is a Well-known Complication Of Spinal Cord Injmentioning
confidence: 99%